Marriner S. Eccles and the 1951 treasury: Federal Reserve Accord. Lessons for central bank independence - Thorvald Grung Moe (Levy Economics Institute of Bard College, 2013)
The 1951 Treasury - Federal Reserve Accord is an important milestone in central bank history. It led to a lasting separation between monetary policy and the Treasury's debt-management powers, and established an independent central bank focused on price stability and macroeconomic stability. This paper revisits the history of the Accord and elaborates on the role played by Marriner Eccles in the events that led up to its signing. As chairman of the Fed Board of Governors since 1934, Eccles was also instrumental in drafting key banking legislation that enabled the Federal Reserve System to take on a more independent role after the Accord. The global financial crisis has generated renewed interest in the Accord and its lessons for central bank independence. The paper shows that Eccles's support for the Accord - and central bank independence - was clearly linked to the strong inflationary pressures in the US economy at the time, but that he was as supportive of deficit financing in the 1930s. This broader interpretation of the Accord holds the key to a more balanced view of Eccles's role at the Federal Reserve, where his contributions from the mid-1930s up to the Accord are seen as equally important. For this reason, the Accord should not be seen as the eternal beacon for central bank independence but rather as an enlightened vision for a more symmetric policy role for central banks, with equal weight on fighting inflation and preventing depressions.
Keywords: B31; E52; E58; E63; N12; 330; Marriner Eccles; central banking; monetary policy; fiscal policy